POROSITY AND PERMEABILITY PROPERTIES OF CONSOLIDATED ROCKS OF THE NORTHERN NEAR EDGE ZONE OF THE DNIEPER-DONETSK DEPRESSION - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Paper concerned the researches of porosity and permeability properties of consolidated rocks (siltstones, poor-porous sandstones) of the northern near edge zone of the Dnieper-Donetsk depression. The purpose of the research was to study the petrophysical parameters of the consolidated reservoir rocks, as the basis of the integrated analysis of their physical properties. Such reservoir parameters as the open porosityfactor and void factor, permeability coefficient and residual water saturation factor were studied. Void structure of rocks with capillarimetric method was studied. The relationship of the density of rocks with their porosity was also studied. The porosity study was carried out in atmospheric and reservoir conditions. The bulk density of dry rock samples varies: for siltstones from 2232 kg/m3 to 2718 kg/m3 (mean 2573 kg/m3 ), for sandstones from 2425 kg/m3 to 2673 kg/m3 (mean 2555 kg/m3); water saturated rocks – for siltstones from 2430 to 2727 kg/m3 (mean 2622 kg/m3 ), for sandstones from 2482 kg/m3 to 2688 kg/m3 (mean 2599 kg/m3 ). An apparent specific matrix density varies: for siltstones from 2645 to 2740 kg/m3 (mean 2683 kg/m3 ), for sandstones from 2629 kg/m3 to 2730 kg/m3 (mean 2664 kg/m3). The open porosity coefficient of studied rocks, in a case they were saturated with the synthetic brine, varies: for siltstones from 0,008 to 0,074 (mean 0,034), for sandstones from 0,013 to 0,087 (mean 0,041), if samples were saturated with nitrogene (N2) then it varies: for siltstones from 0,013 to 0,076 (mean 0,040), for sandstones from 0,022 to 0.095 (mean 0.052). The effective porosity factor has following values: for siltstones 0,0003–0,0050 (mean 0,00026), for sandstones 0,0013–0,0293 (mean 0,0048). Analysis of reservoir conditions modeling revealed that porosity coefficient varies: for siltstones from 0,007 to 0,060 (mean 0,028), for consolidated sandstones from 0,011 to 0,081 (mean 0,037). Due to the closure of microcracks under rock loading reduced to reservoir conditions the porosity decreases in comparison with atmospheric conditions, which causes a relative decrease in the porosity coefficient for siltstones from 14 to 19,5 % (mean 17,0 %), for sandstones from 7,5 to 18.0 % (mean 10,5 %). Capillaryometric studies by centrifuging determined that the void space of the studied rocks has the following structure: for siltstones, the content of hypercapillary pores varies from 1 to 6 % (mean 3 %); the content of capillary pores – from 1 to 11 % (mean 5 %), the content of subcapillary pores – from 84 to 97 % (mean 92 %); for sandstones, the content of hypercapillary pores varies from 1 to 18 % (mean 4%); content of capillary pores – from 2 to 40 % (mean 10 %), the content of subcapillary pores – from 43 to 96 % (mean 86 %). According to the results of laboratory measurements of the permeability coefficient, this parameter varies: for siltstones from 0,002 fm2 to 1,981 fm2 (mean 0,279 fm2 ), for sandstones from 0,002 fm2 to 1,492 fm2 (mean 0,176 fm2 ). The correlation analysis has allowed to establish a series of empirical relationships between the reservoir parameters (density, porosity coefficient, permeability coefficient, effective porosity factor and residual water saturation factor). These relationships can be used in the data interpretation of geophysical studies of wells and in the modeling of the porosity and permeability properties of consolidated rocks of the northern near edge zone of the Dnieper-Donetsk depression.
Keywords: porosity and permeability properties; density; residual water saturation; correlation relationships; siltstones; sandstones; effective porosity factor